Concorrência e inovação nos programas de pesquisa da microeconomia Neoclássica e Neoschumpeteriana - Pereira, Tainara Ribeiro (Universidade Federal de São Carlos, 2013)
The existence of several lines of research permeating the field of microeconomics can be seen by the different approaches from each group of authors. This work presents two of such lines using the methodology of scientific research programs proposed by Lakatos. The lines analyzed were the neoclassical theory and neoschumpeterian (or evolutionary) theory. The main objective is to understand the concepts of competition and innovation under these two perspectives. With the secondary purpose of verify some adherence from the modifications in the protective belt of the research program with the observed reality, it was characterized the technical and institutional context for the theoretical formulation. In parallel with the presentation of the contexts that underlie the creation and modification of research programs, it was possible to infer about the progression of each theory. In the neoclassical case, it was argued that the program is degenerating by the side that concerns its changes, because those changes just to explain the puzzles that motivated them. For the neoschumpeterian theory is argued that the research program appears to be progressive, because it alters the protective belt to encompass new facts. Regarding the prevalence of neoclassical theory for economists, it seems that its mathematical formalization was responsible for bringing more enthusiasts, but with the advance of computational methods, the evolutionary model is also promising in this regard.
Competition and Innovation at the Scientific Research Programs of Neoclassical and Neoschumpeterian Microeconomics.
Keywords: microeconomia; economia evolucionária; escola neoclássica de economia; concorrência; inovação; microeconomia neoclássica; microeconomia evolucionária ou neoschumpeteriana; programa de pesquisa científico; competition; innovation; neoclassical microeconomics; neoschumpeterian or evolutionary microeconomics; scientific research program; CIENCIAS SOCIAIS APLICADAS::ECONOMIA